2022
DOI: 10.1111/apa.16607
|View full text |Cite
|
Sign up to set email alerts
|

Duration of clinical symptoms in children with acute respiratory infection

Abstract: Respiratory tract infection (RTI) is one of the most frequent indications for medical care and the prescription of antibiotics in children. 1 During the last decade, molecular diagnostic tools have become widely available for fast, accurate detection of respiratory pathogens associated with RTIs, and several studies using multiplex polymerase chain reaction (PCR) panels for the detection of respiratory pathogens have shown that respiratory viruses are found in 50-90% of children with acute respiratory infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…During respiratory viral infections, nasopharyngeal colonisation with respiratory bacteria including S. pneumoniae , H. influenzae , and Moraxella catarrhalis has been reported to increase in nasal wash samples 20 . Bacterial co‐detections have generally been reported to increase the severity of the respiratory infection 10,18,21 . Social burden associated with the nasopharyngeal detection of respiratory bacteria during acute illness, however, has been scarcely studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During respiratory viral infections, nasopharyngeal colonisation with respiratory bacteria including S. pneumoniae , H. influenzae , and Moraxella catarrhalis has been reported to increase in nasal wash samples 20 . Bacterial co‐detections have generally been reported to increase the severity of the respiratory infection 10,18,21 . Social burden associated with the nasopharyngeal detection of respiratory bacteria during acute illness, however, has been scarcely studied.…”
Section: Discussionmentioning
confidence: 99%
“…The population of this prospective study consisted of children evaluated because of a suspected acute respiratory infection between 1 September 2014 and 31 August 2015 18 . The Ethical Committee of the North Ostrobothnia's Hospital District, Oulu, Finland, found the study plan ethically acceptable (EETTMK 32/2017).…”
Section: Methodsmentioning
confidence: 99%
“…Paalanne et al investigated the duration of clinical symptoms associated with various respiratory viruses in 737 acutely ill children in Finland 3 . They found that 20%–30% of the children experienced clinical symptoms for more than 14 days after the onset of an infection, but only 2%–3% had symptoms that lasted for more than 28 days.…”
Section: Duration Of Clinical Symptoms Varied In Children With Acute ...mentioning
confidence: 99%
“…Specifically, cough lasted for >2 weeks in 18% and for >4 weeks in 3% of rhinovirus infections 3 . The figures varied substantially but not statistically significantly in other smaller virus‐specific groups.…”
mentioning
confidence: 94%
“…Based on the pooled results, cough had resolved in 50% of children by 10 days and in 90% by 25 days 5 . Productive and non‐productive coughs were not reported separately neither in the Finnish study 3 nor in the review 5 . Continuation of productive cough for at least 3 weeks is the main criterion of protracted bacterial bronchitis, and in such cases, beta‐lactam antibiotics are indicated 6 .…”
mentioning
confidence: 99%